2002
DOI: 10.1038/sj.bjc.6600178
|View full text |Cite
|
Sign up to set email alerts
|

The role of reperfusion injury in photodynamic therapy with 5-aminolaevulinic acid – a study on normal rat colon

Abstract: Reperfusion injury can occur when blood flow is restored after a transient period of ischaemia. The resulting cascade of reactive oxygen species damages tissue. This mechanism may contribute to the tissue damage produced by 5-aminolaevulinic acid-induced photodynamic therapy, if this treatment temporarily depletes oxygen in an area that is subsequently reoxygenated. This was investigated in the normal colon of female Wistar rats. All animals received 200 mg kg 71 5-aminolaevulinic acid intravenously 2 h prior … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 26 publications
1
13
0
Order By: Relevance
“…In a previous study [29] we showed that if the dark interval is introduced later during illumination, the effect is much less. It was postulated that the first light fraction causes temporary vascular occlusion and that the dark interval permits re-vascularization which re-oxygenates the target tissue (making light delivered after the dark interval more effective) as well as producing a re-perfusion injury [31]. The first light fraction may also consume available oxygen in the tissue faster than oxygen can be delivered via the blood, although this is less likely as reducing the light fluence rate produces a much smaller enhancing effect with ALA than with some other photosensitizer [37,38].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous study [29] we showed that if the dark interval is introduced later during illumination, the effect is much less. It was postulated that the first light fraction causes temporary vascular occlusion and that the dark interval permits re-vascularization which re-oxygenates the target tissue (making light delivered after the dark interval more effective) as well as producing a re-perfusion injury [31]. The first light fraction may also consume available oxygen in the tissue faster than oxygen can be delivered via the blood, although this is less likely as reducing the light fluence rate produces a much smaller enhancing effect with ALA than with some other photosensitizer [37,38].…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism of this has been shown to be oxygen depletion induced during the initial light period by temporary vascular constriction being reversed during the dark period. This results in tissue re-oxygenation, which enhances the PDT effect when light delivery is resumed [30] as well as leading to reperfusion injury [31].…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, the activities of key antioxidant enzymes involved in maintaining redox homeostasis and protecting against oxidative stress were significantly higher in cells cultured under hyperoxia (Fig. 4) and have previously been shown to confer resistance to photodynamic therapy, chemotherapy and radiotherapy both in vitro and in vivo [42][43][44][45][71][72][73]. Further investigation found that selective inhibitors of the Nrf2-regulated thioredoxin antioxidant system increased the efficacy of photodynamic cell killing under physioxia, but not under hyperoxia (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…CAT, GPX1, PRDX1 and TXN [42][43][44][45]), apoptosis (e.g. CASP3, BCL2 and BAX [46]) and haem biosynthesis (e.g.…”
Section: Adaptation To Hyperoxic Conditions Significantly Enhances Bamentioning
confidence: 99%
“…Effective reoxygenation of cells can occur in dark periods of around 30-150 s, depending on the degree of induced hypoxia and on the intactness of the microcirculation [20,47]. Reperfusion injury can occur during PDT when blood flow is restored after a transient period of ischemia [48]. Furthermore, relocalization of the photosensitizer during the dark period may occur and improve the outcome [49].…”
Section: Fractionated Light Exposurementioning
confidence: 99%